2008
DOI: 10.1002/cbf.1534
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of aminoguanidine against oxidative stress and bladder injury in cyclophosphamide‐induced hemorrhagic cystitis in rat

Abstract: Cyclophosphamide (CP) is an antineoplastic agent that is used for the treatment of many neoplastic diseases. Hemorrhagic cystitis (HC) is a major dose limiting side effect of CP. Recent studies show that aminogaunidine, an inhibitor of inducible nitric oxide synthase is a potent antioxidant and prevents changes caused by oxidative stress such as depletion of antioxidant activity and tissue injury. The purpose of the study is to investigate the effect of aminoguanidine on parameters of oxidative stress, antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…These include α-tocopherol, β-carotene, taurine, and melatonin [4][5][6]. In a recent study, we have shown that aminoguanidine pretreatment attenuates CP-induced oxidative stress, decrease in the activities of antioxidant enzymes, and reduced bladder damage [25].…”
Section: Discussionmentioning
confidence: 99%
“…These include α-tocopherol, β-carotene, taurine, and melatonin [4][5][6]. In a recent study, we have shown that aminoguanidine pretreatment attenuates CP-induced oxidative stress, decrease in the activities of antioxidant enzymes, and reduced bladder damage [25].…”
Section: Discussionmentioning
confidence: 99%
“…Excess NO levels have been linked to changes in epithelial barrier function in a number of pathologies including BPS/IC (175,231). Studies have shown that both aminoguanidine and TGF-␤1 inhibit expression of iNOS and have been shown to prevent changes in urinary bladder following cyclophosphamide treatment in rats (1,162).…”
Section: Nomentioning
confidence: 99%
“…However, the correlation between changes in protein glycation and ␤-cell glucotoxic alterations was rather poor in these studies, thereby raising questions about the causal link between both events (24,39). It is indeed possible that the beneficial effects of aminoguanidine on ␤-cell glucotoxicity may be unrelated to the reduction in protein glycation but rather depend, like those of NAC, on the reduction of oxidative stress (1,17). Despite the lack of effect of FN3K deficiency on ␤-cell function after culture in G10 and G30, our study does not formally exclude the possibility that protein glycation plays a role in ␤-cell glucotoxicity.…”
Section: Discussionmentioning
confidence: 86%